Recent progress of cryogenic system for 40 T hybrid magnet. Issue 1 (November 2015) - Li, J; Ouyang, Z; Li, H; Meng, Q; Shi, L; Ai, X; Fang, M; Chen, X
Abstract: The 40 T hybrid magnet under construction at High Magnetic Field Laboratory of Chinese Academy of Sciences (CHMFL) consists of an 11 T superconducting outsert with clear bore of 800 mm and a resistive insert with clear bore of 32 mm. The outsert made of Nb3 Sn CICC is cooled with 4.5 K forced flow helium. The main cryogenic system includes a helium refrigerator (360 W at 4.5 K) and a helium distribution system for the cooling of coils, structures, transfer line and current leads. The helium refrigerator was successfully commissioned and put into operation in 2012. The helium distribution system installation will be completed in December 2015. This paper discusses the design of cryogenic system and recent progress in construction.